Non-communicable diseases in Saudi adolescents: prevalence, risk factors, and implications for public health - Almuqbil, Mansour; Rabbani, Syed Imam; Gilkaramenthi, Rafiulla; Aljawadi, Mohammad; Alsanie, Walaa F.; Alamri, Abdulhakeem S.; Alhomrani, Majid; Alrouwaijeh, Sara; Alshammary, Amal F.; Imran, Mohd; Asdaq, Syed Mohammed Basheeruddin (Frontiers in Public Health, 2025)
ObjectivesThis study aimed to assess the prevalence of non-communicable diseases (NCDs) among Saudi adolescents, focusing on obesity, conduct disorder, asthma, and anxiety, and to identify potential risk factors associated with these conditions.MethodsA retrospective cross-sectional analysis was conducted using data from 2,160 adolescents sourced from official government databases and peer-reviewed literature. Statistical methods included one-way ANOVA, chi-square tests, logistic regression, and Pearson’s correlation coefficient, with significance set at p < 0.05 and a 95% confidence interval.ResultsThe prevalence of NCDs among Saudi adolescents was 11.8%. Obesity was the most common condition (odds ratio [OR] = 1.24, p = 0.006), followed by conduct disorder (OR = 1.12, p = 0.041), asthma (OR = 1.09, p = 0.036), and anxiety (OR = 1.06, p = 0.042). Pearson’s correlation revealed significant associations between these disorders and adolescence stages.ConclusionObesity, conduct disorder, asthma, and anxiety are significant health challenges for Saudi adolescents. These findings highlight the role of lifestyle factors such as diet and physical inactivity. Targeted interventions are needed to promote healthy behaviors and mitigate the long-term risks of these conditions.